Effect of Giving Ethanol Extract of Palm Fruit (Arenga pinnata Merr.) on The Lipid Profile of White Rats (Rattus norvegicus L.) Induced by Carbon Tetrachloride (CCl4) - Rendi Ardiansyah Rambe; Husnarika Febriani; Syukriah Syukriah (BIOPENDIX, 2025)
Carbon tetrachloride (CCl4) is a chemical substance in the form of a clear liquid, volatile and toxic with a sweet odor. Palm fruit (Arenga pinnata Merr.) is a plant that has high antioxidants and is able to reduce the effects of free radicals in the body. The purpose of this study was to evaluate the impact of ethanol administration of palm fruit (Arenga pinnata Merr.) on total cholesterol, triglyceride, HDL and LDL levels of white rats (Rattus norvegicus L.) which were induced by carbon tetrachloride (CCl4). This study used a completely randomized design with 20 mice divided into 5 treatments and 4 replications. Negative controls were given food and drink, positive controls were given carbon tetrachloride 1 mL/kg BW + olive oil ratio 1:3, Treatments 1,2, and 3 were given carbon tetrachloride 1 mL/kg BW + olive oil with a ratio 1:3 + palm fruit ethanol extract in graded doses (P1=90, P2=180, and P3=360 mg/kg BW) for 15 days. Data analysis used one way ANOVA and continued with the Duncan test. The results showed that 1 mL/kg BW of carbon tetrachloride could damage the lipid profile of white rats. Giving ethanol extract of palm fruit (Arenga pinnata Merr.) to P1 and P2 at a dose of 90 mg/kg BW and 180 mg/kg BW had no significant effect. Meanwhile, P3 with a dose of 360 mg/kg BW had a significant effect on reducing total cholesterol, triglyceride and LDL levels and could significantly increase HDL levels at a significant level (p<0.05).